El efecto socioeconómico de los hard discount en las tiendas de barrio ciudad de Bogotá (2023)
The Hard Discount has been implemented in Colombia, the remarkable results obtained by foreign businessmen have motivated local businessmen to implement this business style at the national level. The study of consumer needs, such as low prices on basic household products, and easy access to products that are kept at high prices in conventional stores and the purchase and sale of national products, have made Hard Discount not not only a market protagonist but also enemy number 1 for small stores, which offer their products to their neighbors and visitors to their neighborhoods.